Infant brain response to affective and discriminative touch: A longitudinal study using fNIRS. - Miguel, H. (2018)
The affective-motivational component of touch has been shown to consistently activate the social- brain network in children, adolescents and adults, including the posterior superior temporal sulcus (pSTS). However, very little is known about the neural mechanisms of affective touch processing during the first year of life. The objective of the present study was to analyze brain response to affective and discriminative touch in a sample of seven-month-old infants (N = 35) who were followed longitudinally at 12 months of age (N = 25). Infants were given affective and discriminative touch to the bare forearm while their brain response was recorded using functional near-spectroscopy (fNIRS). Seven-month-olds presented brain activation for affective and discriminative stimuli in channels placed over the somatosensory region, but no activation was recorded in channels placed in the temporal region for affective touch. At 12 months of age, infants presented a significant increase in hemodynamic activity in channels placed over the temporal region for affective touch, compared to seven-month-olds. Our study presents evidence of a developmental trajectory for distinct aspects of touch brain processing in the first year of life, with the recruitment of the temporal region for the affective component of touch, maturing in the second semester of life.